2019
DOI: 10.22456/1679-9216.92100
|View full text |Cite
|
Sign up to set email alerts
|

Estimation Metabolic Status in High Yielding Dairy Cows During Transition Period and Full Lactation

Abstract: Background: Major changes in the metabolic functions in high-yielding dairy cows occur during the transitional period and during lactation. Parturition and lactogenesis are accompanied by many physiological changes that facilitate the maintenance of homeostasis Consequently, physiological situations leading to a negative energy balance are coupled to an increased uncontrolled rate of body fat mobilisation and the increased fatty acids accumulation in hepatocytes and blood ketone bodies, resulting in disturbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…Blood glucose concentrations in cows with SCK and CK statistically significantly decresead (P<0.001), as a result of depletion of glycogen from the liver (West, 1990;Drackley et al, 2001;Marutsova & Marutsov, 2016). The changes in the development of SCK and CK in the cows of the three groups established by us and by other authors (Bertoni et al, 2010;Djoković et al, 2013) showed that the pigmentary function of the liver is disturbed, as seen from increased (P<0.001) total bilirubin concentrations, particularly obvious in recently calved and lactating cows with SCK and CK. The impaired pigmentary function of the liver (bilirubinaemia) is due to the dystrophic changes, which on one hand, mechanically obstruct bilirubin secretion in the bile and, on the other, disturb permeability of bile and blood capillaries in the damaged hepatocytes (karyopyknosis and karyolysis, lipidosis, etc.).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Blood glucose concentrations in cows with SCK and CK statistically significantly decresead (P<0.001), as a result of depletion of glycogen from the liver (West, 1990;Drackley et al, 2001;Marutsova & Marutsov, 2016). The changes in the development of SCK and CK in the cows of the three groups established by us and by other authors (Bertoni et al, 2010;Djoković et al, 2013) showed that the pigmentary function of the liver is disturbed, as seen from increased (P<0.001) total bilirubin concentrations, particularly obvious in recently calved and lactating cows with SCK and CK. The impaired pigmentary function of the liver (bilirubinaemia) is due to the dystrophic changes, which on one hand, mechanically obstruct bilirubin secretion in the bile and, on the other, disturb permeability of bile and blood capillaries in the damaged hepatocytes (karyopyknosis and karyolysis, lipidosis, etc.).…”
Section: Resultssupporting
confidence: 62%
“…The decrease in total protein in the early lactation can also be explained by redirecting albumin and globulins from the blood to the udder. The hypoproteinaemia in cows with ketosis is due to the dystrophic processes and fatty infiltration of the liver and kidneys (Djoković et al, 2013;Аbba et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that animals in the experiment were in a positive energy balance. In certain cases when the animal suffers from water deprivation and thirst or has diseases such as diarrhea, urinary diseases, pregnancy toxemia, and acidosis, the BUN level might increase (22). However, these conditions were not present in cows used in this study.…”
Section: Discussionmentioning
confidence: 75%
“…These findings are in accordance with Shin et al (2015), who observed a lower value of the protein indicators in cows with ketosis when compared with non‐ketotic cows. In addition, decreased serum urea and total protein concentrations have been reported in cows with high lipomobilization and ketogenesis during early lactation compared to healthy cows (Djokovic et al, 2019). This reduction may have occurred due to reduced dry matter intake associated with reduced hepatic ureagenesis (Strang et al, 1998).…”
Section: Discussionmentioning
confidence: 99%